Urban–rural school-age population changes and compulsory education resource allocation - Guo, Dong-Yang (Frontiers in Education, 2025)
IntroductionTo address disparities in compulsory educational resource allocation and foster integrated urban-rural education, it is crucial to understand how resources respond to demographic shifts. This study examines current allocation patterns and their relationship to changes in the school-age population.MethodsThe research utilizes data from the China Statistical Yearbook.ResultsData analysis reveals that increasing urbanization has caused a significant decline in the rural school-age population, altering the demographic balance between areas. Regarding resources, while the overall quantity of teachers is sufficient, regional disparities persist. Similarly, while education funding exhibits steady growth, the urban-rural gap is widening.DiscussionThe size of the school-age population and economic conditions are the predominant factors influencing resource allocation. Despite improvements in physical infrastructure, structural inequities such as teacher shortages and funding gaps remain, necessitating targeted policy interventions to achieve true integration.